Staropolskie słownictwo prawnicze w łacińskim kontekście (na przykładzie ksiąg sądowych) - Maria Trawińska (Język. Religia. Tożsamość, 2021)
The article presents preliminary findings concerning the legal vocabulary found in medieval Latin-Polish court books. On the basis of various entries related to the lien law, it has been shown that many Latin fragments of monuments abound in names derived from the Roman law, which then were replaced with the equivalent Polish names. However, the way writers have used them makes it very difficult to determine their contextual meaning.